Landscape of Global Gene Expression Reveals Distinctive Tissue Characteristics in Bactrian Camels (Camelus bactrianus) - Luan, Yuanyuan; Fang, Yan; Jiang, Lin; Ma, Yuehui; Wu, Shangjie; Zhou, Junwen; Pu, Yabin; Zhao, Qianjun; He, Xiaohong (Agriculture (Basel), 2022)
Bactrian camels (Camelus bactrianus) are highly adapted to the desert and semi-desert environments of Asia and developed unique physiological adaptations to cold, heat, drought, and nutrient-poor conditions. These animals are an ideal model for studying desert adaptation. However, the transcriptome of different Bactrian camel tissues has not been profiled. This study performed a comprehensive transcriptome analysis of nine fetal and adult tissues. A total of 20,417 coding genes were identified, and 2.4 billion reads were generated. Gene expression and functional analyses revealed that approximately 50% of the identified genes were ubiquitously expressed, and one-third were tissue-elevated genes, which were enriched in pathways related to the biological functions of the corresponding tissue. Weighted gene co-expressed network analysis (WGCNA) identified four modules—fat metabolism, water balance, immunity, and digestion—and several hub genes, including APOA1, TMEM174, CXCL12, and MYL9. The analysis of differentially expressed genes (DEGs) between fetal and adult tissues revealed that downregulated genes were enriched in tissue development, whereas upregulated genes were enriched in biological function in adult camels. DEGs in the hump were enriched in immune-related pathways, suggesting that this tissue is involved in immunity. This study is the first to generate a transcriptome atlas of major tissues in Bactrian camels and explores the genes potentially involved in the adaptation to desert environments.